PELAKSANAAN PEMBELAJARAN SAAT MASA PANDEMI COVID-19 DI KELAS IV C SDN 35 PONTIANAK SELATAN - Nosa Rianti; Hamdani Hamdani; Asmayani Salimi (Universitas Tanjungpura, 2022)
Based on the background presented that the learning process will still becarried out even with limited face-to-face, then researchers are interested inconducting research to know the implementation of learning during thepandemic, then the researcher formulated a common problem of this study ishow to implement learning during the covid-19 pandemic. The purpose is todescribe how to implement learning during the covid-19 pandemic in gradeIV C. The research method used is qualitative research. This type of researchis descriptive research. Research location in the field. The research subjectconsists of teachers and students. Research data sources include primary andskunder data. Data collection techniques with observation, interview, anddocumentation techniques. The results showed that the implementation oflearning has been running face-to-face but the results have not been effective,student learning outcomes are still relatively low because it is difficult toassess objectively, student activities while in school are still not good, studentresponses to learning activities vary, namely some who receive well there arealso still adapting, and there are still factors that support and inhibit theongoing learning activities.Keywords: Activities, Implementation of Learning, Inhibitory andSupporting Factors, Learning Outcomes